PAISAGEM, ESPAÇO E TERRITÓRIO - ALVES, Adilson Francelino; RIBAS, Alexandre Domingues; CANDIOTTO, luciano Z. P.; SAQUET, Marcos Aurélio; SANTOS, Roseli Alves dos (Formação (Online), 2011)
Este texto revela aspectos de nossa preocupação teórico-conceitual...